Effects of Human-Social Capital Congruence and Environmental Dynamism on Dynamic of Encouragement and Organizational Innovation in New Ventures - Lu, Yurong; Cai, Wendi; Bi, Xiaoliang (Frontiers in Psychology, 2022)
Although human capital and social capital are broadly defined as resources provided by knowledge and social network available to organizations, existing studies are inadequate to explore how the two types of capital interact in shaping organizational behaviors or organizational outcomes. In this study, we investigates whether the relationship of human capital and social capital was compensatory or complementary, and how their impact on organizational innovation in consideration of dynamic of encouragement. Using data from more than 200 technology-new ventures in China, we analyze the associations among all the parameters through bootstrapping and response surface methods. The findings suggest that 1) organizational innovation is stronger when human and social capital are congruent; 2) the dynamic of encouragement fully mediates the relation between capital congruence and organizational innovation performance. Furthermore, 3) environmental dynamism positively moderates the relationship between capital congruence and dynamic of environment, in such a way that the relationship is stronger for new ventures in higher dynamic environments rather than lower. Finally, the theoretical and managerial implications of this study are discussed.